The Older Adults Experience Caring for Grandchildren with Special Needs - Sylvia Dwi Wahyuni; Retno Indarwati; Aditya Budi Nugroho (Universitas Airlangga, 2021)
Introduction: Nowadays, grandparents are still involved in the care of grandchildren. The previous research showed that the grandparent involvement in the care of grandchildren has a bad and good impact for older adults. This study aims to gain a deep understanding of the experience of older adults while caring for their grandchildren with special needs.Methods: Researchers use a phenomenological approach to explore the experience based on awareness that occurs in some individuals. The participants involved in this study were six older adults. Data were collected by in-depth interview and analyzed by Colaizzi’s method.Results: All participants have grandchildren who attended school for special needs childrenin Surabaya city. This study showed all participants responded positively and related involvement in taking care of grandchildren. In addition, the decision to being a part of caring for the grandchildren came from themselves and the discussions with both parents. Most of the activities with grandchildren were spending time together. However, all participants complained of being tired and this condition can be solved by seeing grandchildren’s happiness. They believed that grandchildren care is better with grandmothers or grandfathers than with servants.Conclusion:It can be concluded that the experiences of the older adult taking care of grandchildren are very varied and positive for the older adults. Further researchers are advised to continue to explore more detail about the psychological influence of grandparents taking care of their grandchildren with special needs.